Early Reading through Storytelling Activities - Kristi Nuraini (Ahmad Dahlan Journal of English Studies, 2020)
Storytelling has been a part of children’s life. They loved being told as well as telling a story. Being told a story made them see what has been read, and telling a story made them talk as they spoke it out. As the children learn a language, story is one effective way for them to learn a language. This study is aimed to find out to what extent storytelling could help young children with their early reading comprehension in terms of story-retell. One class in one national plus school has been the setting of the study with 13 students as the subjects. A mix method was implemented through a classroom action research design. This study came up with a significant result that storytelling activities have been effective ways to increase young children’s retell fluency, both in content and fluency. The help of pictures, cue cards, and flashcards has been very efficient in helping young children to have a better comprehension in their early reading. These teaching aids had also been able to motivate them to be more active and engaged during the class.